2014
DOI: 10.1007/s12182-014-0364-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of diagenetic trap formation in nearshore subaqueous fans on steep rift lacustrine basin slopes—A case study from the Shahejie Formation on the north slope of the Minfeng Subsag, Bohai Basin, China

Abstract: Diagenetic traps in conglomerate in nearshore subaqueous fans in the steep slope zones of fan conglomerates and carbonate cementation of conglomerates adjacent to mudstone layers in middle fan braided channels took place from 32 Ma B.P. to 24.6 Ma B.P., thus the formation of diagenetic traps was from 32 Ma B.P. to 24.6 Ma B.P. and diagenetic traps have a better hydrocarbon sealing ability from 24 Ma B.P.. The sealing ability of inner fans gradually increases with the increase of burial depth and diagenetic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…) has shown that the depositional systems along the margin of this ancient basin can be divided into three categories related to three structural subregions: faulted margin depositional systems in the north, hinged margin depositional systems in the south and axial margin depositional systems in the east and west. The northern faulted margin depositional systems are proximal systems that include fan deltas and sublacustrine fans associated with storm deposits and turbidites (Li et al ., ; Liu & Wang, ; Feng et al ., ; Wang et al ., , ); the bathymetric gradient was great there. The southern hinged margin was occupied by an extensive shore‐shallow lake system with a low bathymetric gradient (Jiang et al ., ) where large‐scale beach‐bar systems developed (Li et al ., ; Jiang et al ., , ).…”
Section: Application To the Eocene Dongying Depressionmentioning
confidence: 99%
“…) has shown that the depositional systems along the margin of this ancient basin can be divided into three categories related to three structural subregions: faulted margin depositional systems in the north, hinged margin depositional systems in the south and axial margin depositional systems in the east and west. The northern faulted margin depositional systems are proximal systems that include fan deltas and sublacustrine fans associated with storm deposits and turbidites (Li et al ., ; Liu & Wang, ; Feng et al ., ; Wang et al ., , ); the bathymetric gradient was great there. The southern hinged margin was occupied by an extensive shore‐shallow lake system with a low bathymetric gradient (Jiang et al ., ) where large‐scale beach‐bar systems developed (Li et al ., ; Jiang et al ., , ).…”
Section: Application To the Eocene Dongying Depressionmentioning
confidence: 99%
“…It is a Mesozoic-Cenozoic half graben rift-downwarped basin with lacustrine facies directly deposited on Paleozoic bedrocks (Cao et al 2014;Wang et al 2014b). The Dongying Sag is bounded to the east by the Qingtuozi Salient, to the south by the Luxi Uplift and Guangrao Salient, to the west by the Linfanjia and Gaoqing salients, and to the north by the Chenjiazhuang-Binxian Salient.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…This issue has been studied many times. Although the controlling factors of the formation of deep, abnormally high porosity zones vary in different regions, most geologists generally believe that mineral dissolution, shallow fluid overpressure, early hydrocarbon charging, and grain rims are the main factors that control the development of deep AHPZs (Bloch et al 2002;Ehrenberg 1993;Warren and Pulham 2001;Meng et al 2011Meng et al , 2010Taylor et al 2010;Wilkinson and Haszeldine 2011;Cao et al 2014;Yuan et al 2015;Ajdukiewicz and Larese 2012;Wang et al 2014;Jiang et al 2009). …”
Section: Introductionmentioning
confidence: 99%